…ne quem magistratum, cui provincia obvenisset, uxor comitaretur (tac. ann. 3, 33, 4): presenze femminili al seguito di magistrati e militari nelle province - Albana, Mela (Studia Europaea Gnesnensia, 2017)
In the early Imperial age, a feature, which had already been seen in the period of civil wars, even though sporadically and disapproved, took hold and became almost commonplace: wives increasingly accompanied their husbands who were sent to the provinces on military and civilian duties. Already with Augustus, but especially with the first and second generation Princes, it was established the custom that the women of the domus imperialis accompanied their husbands engaged away from Rome: the image of a couple united in sharing the daily toils of military life as well as the honours of public ceremonies was functional to prestige and the idea of a potential imperial succession. Even some Governors’ wives moved to the provinces but not all of them chose to live in the shadows, some entering forbidden areas and subsequently being involved in trial for concussio. The custom of accompanying their husbands inevitably spread also among wives of ordinary soldiers. Despite attempts to revive the old bans, the mos maiorum (Tac. Ann. 3, 33, 4), strenuously defended by the conservatives in tones reminiscent of Cato the Elder, was superseded by the new behaviours promoted by the members of the domus Augusta.